A Power System Stabilizer for Multi-Machine Power Based on Hybrid BF0A-PSO - Mary Saranya; Rajapandiyan A; Fathima K.; Hema S; GeethaPriya S; Saravanan S (Institute of Advanced Engineering and Science, 2015)
Bacterial Swarm Optimization (BSO) is used to design Power System Stabilizers in a multi machine power system. In BSO, the search directions of tumble behavior for each bacterium are oriented by the individual’s best location and the global best location of PSO. The hybrid BFOA-PSO algorithm has been applied to IEEE 14 bus test system under normal, light and heavy load conditions. Simulations results have revealed the strength of the BSO in tuning Power System Stabilizers under normal, light and heavy load conditions. The results present the effectiveness of the controller to improve the power system stability over a different range of loading conditions.